PELATIHAN MANAJEMEN OPERASI DAN AKUNTANSI BIAYA PADA NASI PECEL MBAK YANI - Adi Mansah; Muhammad Ikra; Ferly Aninditya; R. Melda Maesrach (Taksasila Edukasi Insani, 2025)
Micro, small and medium enterprises (MSMEs) such as the Nasi Pecel Mbak Yani food stall have an important role in driving the local economy. However, challenges in managing operations management and recording cost accounting are still major obstacles to business efficiency and sustainability. This community service activity aims to provide training and assistance in the field of operations management and cost accounting. The method used is a participatory approach through training, discussion, and direct practice. The results of the activity show an increase in partners' understanding of the importance of managing the production process, controlling costs, and systematic recording. This training encourages MSMEs to be more efficient, competitive, and sustainable.Keywords: MSMEs, operations management, cost accounting, training, community service